Monetary policy and redistribution in open economies - Xing Guo; Pablo Ottonello; Diego J. Perez (Bank of Canada, 2022)
This paper examines how monetary policy affects the asymmetric effects of globalization. We build an open-economy heterogeneous-agent New Keynesian model (HANK) in which households differ in their income, wealth, and real and financial integration with international markets. We use the model to reassess classic questions in international macroeconomics, but from a distributional perspective: What are the effects of monetary policy and external shocks in open economies? And how do alternative exchange-rate regimes compare? Our analysis yields two main takeaways. First, heterogeneity in households' international integration is a central dimension that drives the inequality in the consumption responses to external shocks more so than do income and wealth. Second, households' heterogeneity reveals the presence of a stabilization-inequality trade-off for the conduct of monetary policy in open economies, with fixed exchange-rate regimes leading to amplified but less unequal consumption responses to external shocks.
Keywords: E32; E52; F41; F44; 330; Monetary policy; Exchange rate regimes